Application of pelvic floor ultrasound during pregnancy to detect patients at risk of cesarean section due to failure of labor progression in a Spanish population. (February 2022) - Guntiñas, Alicia; Galocha, Carolina; Madurga, Rodrigo; Kirk, Janette; Usandizaga, Ramón; Ángel Rodríguez-Zambrano, Miguel
Highlights: . Transperineal ultrasound is useful for the study of the pelvic floor in pregnancy. . The patients who gave birth by cesarean section had a smaller hiatal area of levator ani. . The greater the hiatus area, the greater the possibility of vaginal delivery. . This is independent of age and BMI. Abstract: Objective: Our study is aimed at evaluating the characteristics of the pelvic floor, assessed through transperineal ultrasound, since it may influence or increase the possibility of having a cesarean delivery, with the objective of acting on those variables that can be modified during pregnancy. Study Design: Transperineal ultrasound was performed on 109 primiparous pregnant women in their first trimester of pregnancy, recruited between May 2018 and February 2019, with the purpose of studying the hiatus area at rest, retention and Valsalva. We have reassessed them at the end of pregnancy and delivery data were recorded. We selected 8 patients as case-study, who had cesarean section delivery due to failure of labor progression. We selected 4 control-cases for each, reaching the total of 32 controls, with similar age and body mass index, to avoid obtaining a biased result from these data. Results: In the study of hiatal areas, patients who delivered by cesarean section had a smaller hiatal area at rest, during levator ani muscle contraction and during Valsalva maneuver, at all visits. In early pregnancy, the range of the resting hiatal area was 13.8 ± 2.0 cm 2 for cesarean sections, compared to 16.2 ± 2.7 cm 2 for vaginal deliveries with an OR of 0.57 (0.34–0.95, 95% CI). For hiatal area on Valsalva, the OR was 0.55 (0.35–0.88, 95% CI). Therefore, the smaller the hiatal area, the greater the possibility of cesarean section. At the end of pregnancy, between 34 and 36 weeks of gestation, the OR of hiatal area on Valsalva was 0.78 (0.60–1.00, 95% CI). Conclusion: The hiatus area measured by transperineal ultrasonography at the beginning and at the end of the pregnancy may be useful to identify the patients who are at a higher risk of cesarean delivery due to failure of labor progression.